The Cancer Mortality in High Natural Radiation Areas in Poland - Krzysztof Wojciech Fornalski; Ludwik Dobrzyński (SAGE Publishing, 2012)
The cancer mortality ratios (CMRs) in Poland in high and low level radiation areas were analyzed based on information from national cancer registry. Presented ecological study concerned six regions, extending from the largest administration areas (a group of voivodeships), to the smallest regions (single counties). The data show that the relative risk of cancer deaths is lower in the higher radiation level areas. The decrease by 1.17%/mSv/year (p = 0.02) of all cancer deaths and by 0.82%/mSv/year (p = 0.2) of lung cancers only are observed.